Shipsheds of the ancient Mediterranean - Blackman , David (Cambridge University Press, 2013)
"This is the first detailed and comprehensive study of the shipshed complexes which housed the great navies of the Greco-Roman world, including Athens and Carthage. These complexes represented some of the largest and most expensive building projects of antiquity, and the volume provides a comprehensive survey of the archaeological and literary evidence for them. It explains how the buildings were carefully designed to keep warships dry and out of reach of shipworm, whilst enabling them to be launched quickly, easily and safely when required. It also serves as a handbook for archaeologists who may excavate such buildings, which are often difficult to interpret. The analytical chapters are complemented by a full and detailed catalogue of known sheds, with plans for all the major sites specially drawn for easy comparison. The book thus provides an indispensable guide for all those interested in these buildings and in the maritime infrastructure of the ancient world"--